Polymorphism in HTR3D shows different risks for acute chemotherapy-induced vomiting after anthracycline chemotherapy - Hammer, Christian; Fasching, Peter Andreas; Loehberg, Christian R; Rauh, Claudia; Ekici, Arif B.; Jud, Sebastian M.; Bani, Mayada R.; Beckmann, Matthias Wilhelm; Strick, Reiner; Niesler, Beate (Pharmacogenomics, 2010)
Aims: Serotonin (5-hydroxytryptamine 3; 5-HT3) receptors are involved in chemotherapy-induced nausea and vomiting (CINV), and 5-HT3 antagonists are part of the ‘gold standard’ antiemetic treatment during chemotherapy. We investigated the correlation of common variants in 5-HT3 receptor subunit genes with the occurrence of CINV. Materials & methods: A total of 110 previously characterized chemotherapy-naive women with primary breast cancer treated with anthracycline-containing chemotherapy served as a study group for mutational analysis by direct sequencing. Eight common SNPs in the 5-HT3 receptor genes, HTR3A, HTR3B, HTR3D and HTR3E, were selected for association analysis. Results: A nonsynonymous variant in HTR3D, p.G36A (rs6443930), was found to be over-represented in nonresponders, assuming a log-additive inheritance model (p = 0.048). Cox proportional regression analysis resulted in a hazards ratio of 0.36 for homozygous carriers of the C allele to vomit within 24 h after first chemotherapy administration (p = 0.049). Conclusion: Our data supports the hypothesis that 5-HT3 receptors play an important role in the pathogenesis of CINV. Along with previously identified HTR3 polymorphisms, the HTR3D p.G36A variant could also contribute to facilitating individual risk predictions.
Gesehen am 03.03.2023